A review burst assembly techniques in optical burst switching (OBS) - A. Yayah, Abdul Salam (Penerbit UTM Press, 2015)
Optical Burst Switching (OBS) is perceived as the most favorable switching method for the next generation all optical networks to support the growth of the number of Internet users and to satisfy bandwidth demands for greedy-bandwidth applications which are in continuous growth. OBS consists of an edge node and a core node. The edge node is responsible for burst assembly which is the first process in an OBS network. Currently, there is only one review paper for burst assembly; the paper is limited in number of techniques reviewed. In this paper, we have undertaken a comprehensive review of burst assembly techniques proposed for OBS where techniques are reviewed by category. The aim is to identify strengths and weaknesses of these techniques. The analysis of the paper will assist researchers in finding problems; thus, a significant amount of time will be saved which can be used in developing appropriate solutions for OBS networks.